Principles of computer aided design and manufacturing - Amirouche, Farid M. (New Delhi Prentice Hall, 2004)
This book was written with the premise of providing students the necessary foundation to advance understanding of both design and manufacturing. The latter is achieved through selection of appropriate topics and analytical methods in all aspects of design that are pertinent to CAD with the hope that students will embrace them with conviction. These topics, written in a clear and concise form, are followed by examples to guide the students and engineers through a wonderful learning experience. In essence, CAD should provide the engineer more time to be creative, to conceptualize and formulate the problem definition, and interpret results derived from the analysis. The author philosophy is to teach through examples; hence, every topic covered is followed by examples to demonstrate the concepts. The basic engineering concepts covered in this book are independent of any specific software. This textbook allows students to perform their exercises using MATLAB to facilitate the understanding that CAD is multidisciplinary in nature and that part of the design could be performed in conjunction with other programs or programming tools. This is definitely true in the variational design and parametric designs, where engineering equations are the engine behind the geometrical formulation and design of certain products. Chapter 1 introduces a historical perspective of CAD/CAM and discusses virtual reality as it is used in our current engineering environment. Chapter 2 addresses the different stages in design and provides a concrete example of how these steps are accomplished. The unique feature of this chapter is the parametric and variational design concept. Chapter 3 concerns 2D and 3D transformations and geometry manipulation. It provides an in-depth analysis of images in 2D and 3D) including isometric views. Chapter 4 explains the fundamentals underlying splines, curves parametric and nonparametric, Bezier curves, and surfaces. Chapter 5 introduces the concept of solid modeling and the various construction techniques and representation schemes in modeling. Students should enjoy this chapter as they apply some of these concepts in their Lab work working with the making of solid models in CAD. Chapter 6 covers various techniques of optimization to introduce students to the basic concept of how to formulate an objective function, define the appropriate constraints, and choose the analytical tools to solve the problem. This chapter focuses on combining popular techniques in optimization to which most students at this level are going to be exposed. Chapters 7-10 form a unique combination of teaching the finite element method to junior- and senior-level students without the burden of heavy calculus, this being one of the strengths of this book. Depending on the curriculum, all chapters can be covered if analysis is heavily weighted, or else the instructor has the option of choosing to cover FEM through several means. These include stresses, heat conduction, dynamic analysis and vibration, or simply teaching the basic formulation of the finite element method as described in Chapter 7. The examples solved in these chapters represent real applications and should encourage the appetite of students for FEM. Computer-aided manufacturing is introduced in Chapters 11-15. This part of the book focuses on topics of interest to students, including robotics and economic impact, group technology, and computer integrated manufacturing.